ChemInform Abstract: Sol—Gel Synthesis and Room‐Temperature Properties of α‐LiZr2(PO4)3. Issue 21 (May 2015) - El‐Shinawi, Hany; Greaves, Colin; Janek, Juergen
Abstract α‐LiZr2(PO4)3 is prepared by a sol‐gel approach from a stoichiometric solution of Li(OAc) and ZrO(NO3)2 in HNO3 to which EDTA and citric acid is given at pH <7.